2009
DOI: 10.1088/0953-2048/22/7/075012
|View full text |Cite
|
Sign up to set email alerts
|

Melt-textured growth of (LRE)–Ba–Cu–O by a cold-seeding method using SmBa2Cu3Oythin film as a seed

Abstract: A cold-seeding method for fabricating LRE-based (LRE: a light rare-earth element) bulk superconductors under a reduced oxygen atmosphere is reported. We used Sm123/MgO thin films as seed crystals, and succeeded in growing c-axis oriented single grains for both LRE =  Gd and LRE =  Sm. Although a slight contamination of Mg from the seed crystal was detected, high quality bulk superconductors with diameters of 30 mm were successfully fabricated under low oxygen partial pressure. In particular, the trapped field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…However, even Mg-doped Nd-123 seeds are not successful in growing large single-grain samples as in this case for elimination of multiple nucleations one has to increase the maximum temperature by about 80°C above the peritectic temperature of LRE-123 [16]. Recently Oda et al [17] reported use of Sm-123 thin film seed grown on MgO crystal for growing Sm-123 block in the cold seeding process with a reduced oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, even Mg-doped Nd-123 seeds are not successful in growing large single-grain samples as in this case for elimination of multiple nucleations one has to increase the maximum temperature by about 80°C above the peritectic temperature of LRE-123 [16]. Recently Oda et al [17] reported use of Sm-123 thin film seed grown on MgO crystal for growing Sm-123 block in the cold seeding process with a reduced oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a choice of grown materials is limited by thermal stabilities of seed crystals. However, "generic seed" with high thermally and chemically stabilities reported by Shi et al, (MgO-doped NdBCO melt-textured), followed by Yao et al, (Nd-or Sm-123 thin films on MgO substrates) opens a new avenue for growing many variety of (LRE)BCO bulk samples by the cold-seeding method [14][15].…”
Section: -2 Top-seeded Melt Growth (Tsmg) Processmentioning
confidence: 99%
“…In this case, the seed crystal is placed on the precursor pellet at room temperature. For cold seeding of LRE-123 materials two types of seeds have been used: (i) Mg doped LRE-123 melt textured materials [10,11] and (ii) Nd-123 film or Sm-123 film grown on MgO crystal [12,13]. Both types of the seeds had melting temperatures above 1100°C.…”
Section: Introductionmentioning
confidence: 99%